2019
DOI: 10.1111/inr.12526
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy and organizational commitment among Spanish nurses: the role of work engagement

Abstract: Aim The objective of this study was to verify the mediating role of work engagement between self‐efficacy and affective organizational commitment on the basis of the Job Demands‐Resources Model in a sample of Spanish nursing staff. Background Affective organizational commitment is a key element, both for the permanence of nursing staff and for the provision of an excellent quality of care of health organizations. However, the relationships between self‐efficacy, work engagement and affective commitment to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 28 publications
(128 reference statements)
8
43
2
3
Order By: Relevance
“…Such positive effects can also be expected when CI is implemented with the explicit aim to improve employees' working conditions [34,37]. Lower job demands, and in this dynamic task environment, lower stress, as well as related higher work engagement, are of particular importance given the contemporary concerns about the consequences of nurses' high workloads [38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Such positive effects can also be expected when CI is implemented with the explicit aim to improve employees' working conditions [34,37]. Lower job demands, and in this dynamic task environment, lower stress, as well as related higher work engagement, are of particular importance given the contemporary concerns about the consequences of nurses' high workloads [38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…They were also more motivated, persistent and engaged in their work. [33][34][35][36] Social support is another powerful buffer against the adverse effects of emergency stressors and traumatic events, with better social support preventing and reducing the incidence and severity of post-traumatic stress disorder. 37 Moreover, both self-efficacy and social support play an essential role in reducing and ameliorating the adverse effects of traumatic events.…”
Section: Main Findingsmentioning
confidence: 99%
“…Several different focuses and studies have reported the need to seek a consensus with respect to the term, the humanization of care, which would contribute systematically to its development in the field of health [2]. In this respect, previous studies have agreed that the humanization of care is built upon people’s needs in the care relationship [4,10,11,16], for which purpose healthcare professionals must be committed to their work [17,21,22,23], which is promoted if they possess certain characteristics [27,28,29,34,39,40,46].…”
Section: Discussionmentioning
confidence: 99%
“…If the main objective of the humanization of care is to offer the best possible care and satisfy patients’ needs, contact with healthcare professionals committed to that objective is indispensable. Some characteristics seem to be linked to it (Figure 1), for instance, it may be essential for these professionals to be committed to their work, which has already been demonstrated to achieve better results in patient care [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation